Mobile-assisted vocabulary learning through the Shanbay App outside the classroom: Effects of self-regulation and peer scaffolding - Guo, Fengping; Zhang, Yuhan; Wu, Zhixin (Frontiers in Psychology, 2022)
Recent decades have witnessed an increasing academic interest in mobile-assisted vocabulary learning. To explore the possible influencing factors on learning outcomes, this study aimed at examining the effects of self-regulation and peer scaffolding on mobile-assisted vocabulary learning among undergraduate students using Shanbay App beyond the classroom. To this end, altogether 71 intermediate-level English learners aged 17–19 years were chosen as participants, with 37 in the experimental group (with peer scaffolding) and 34 in the control group (without peer scaffolding). Data were collected through the Shanbay App regarding participants’ vocabulary learning performance, a self-regulation questionnaire and semi-structured interviews. The results of factorial ANOVA revealed that peer scaffolding significantly affected mobile vocabulary learning in terms of the days spent in vocabulary learning and the sum of words participants have learned; a main effect of self-regulation and an interaction effect of self-regulation and peer scaffolding were also observed on the sum of learned words. The research is innovative in providing a motivational peer scaffolding framework in mobile vocabulary learning settings, and may provide pedagogical implications for vocabulary teaching in EFL context in higher education.